Pelatihan Komputer Bagi Aparat Desa Tassese Dalam Meningkatkan Kinerja dan Kemampuan Penyusunan Adminstrasi Desa - Raden Wirawan; Agussalim Patola DM; Muhammad Awal Nur (Politeknik Piksi Ganesha Indonesia, 2023)
Computer training in improving the performance and ability of preparing village administration is a community service activity carried out by lecturers at the Bina Adinata Institute of Technology and Business which aims to improve performance and ability to prepare village administration using computers for Tassese Village officials, Village Consultative Body and Village Technical Cadres Tassese. This activity is held every Wednesday on the 8th, 15th, 22nd and 29th of May 2022 at the Tassese Village office, Manuju District, Gowa Regency. This activity is in the form of training on Microsoft Office, including word and excel with the aim of providing convenience in preparing village administration and ease of carrying out financial reporting using a computer. This training also had a positive impact in increasing understanding and knowledge of Microsoft Office for Tassese village officials, thereby increasing performance in using computers in every activity in the village.